Analisis kandungan formalin pada ikan teri (Stolephorus sp) dan perilaku pembeli di Pasar Tradisional Pancur Batu Kabupaten Deli Serdang - Ginting, Puput Puspita; Marsaulina, Irnawati (Talenta Publisher, 2024)
Food safety is a very important aspect in daily life. However, in practice there are still many manufacturers who use food additives that are harmful to health, for example, the use of formalin in anchovies. This type of research is a descriptive survey. The research population is anchovy buyers at the Pancur Batu Traditional Market. The number of samples was 96 buyer taken by accidental sampling method while the object of research was 10 samples of anchovy (Stolephorus sp) taken from different anchovy sellers at the Pancur Batu Traditional Market. The data collection method was carried out by interviews, observation, and laboratory testing using KMnO4 reagent. Data analysis was carried out by univariate analysis. The results showed that 8 out of 10 samples of anchovy (Stolephorus sp) at the Pancur Batu Traditional Market were positive for formalin. Buyers of anchovy at Pancur Batu Traditional Market had good knowledge of 71 people (74,0%), good attitude of 78 people (81,3%) and good actions of 52 people (54.2%). However, there are still quite a number of buyers who do not know and do not make efforts to reduce formalin levels in anchovy. It is hoped that the relevant agencies will carry out further food safety supervision of food sold in the market as well as provide education to the public about formalin in food and it is hoped that consumers will be smarter and more informed in choosing anchovy containing formalin and without formalin and be more aware of the importance of health.